1975
DOI: 10.1037/h0076934
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of pictorial and written adjunct aids in learning from text.

Abstract: The effects of pictorial and written (questions) adjunct aids interspersed through text on factual recall were compared. Sixty-three subjects read one of the following forms of text: questions before relevant passage, questions after, pictures before, pictures after, questions and pictures before, questions and pictures after, no adjunct aids. Results showed that reader-generated pictures and experimenter-provided questions were equally facilitative and resulted in increased retention over the control group. Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 10 publications
3
29
0
Order By: Relevance
“…A final piece of evidence supporting the assessment hypothesis comes from contrasting the studies of Alesandrini (1981) and Snowman and Cunningham (1975). On the surface, these studies are similar.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 87%
See 2 more Smart Citations
“…A final piece of evidence supporting the assessment hypothesis comes from contrasting the studies of Alesandrini (1981) and Snowman and Cunningham (1975). On the surface, these studies are similar.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 87%
“…Alesandrini's (1981) multiple-choice posttest included factual recognition items, but the majority of test items assessed higher-level comprehension or application of ideas. In contrast, Snowman and Cunningham's (1975) multiple-choice posttest included only factual recognition items.…”
Section: The Benefits Of Drawing Construction Are Revealed On Higher-mentioning
confidence: 99%
See 1 more Smart Citation
“…Still other studies have shown that pictures can serve as advance organizers for instructional materials (e.g., Bransford & Johnson, 1972;Brody & Legenza, 1980;Snowman in Cunningham, 1975).…”
Section: Comparisons Of Dual-channel Presentationsmentioning
confidence: 99%
“…These studies embody a wide variety of active learning strategies , including (a) visual or verbal elaboration strategies (e.g., Andre & Sola , 1976;Delaney , 1978;Hunter , 1977;Lyon , 1 977;Rasco , Tennyson , & Boutwell , 1975;Snowman & Cunningham , 1975), (b) generative underlining or sentence generation strategies (e.g., Bobrow & Bower, 1969;Frase & Schwartz, 1975;Rickards & August , 1975) & Gardner , 1976;Carter & VanMatre , 1975;Fisher & Harris , 1973;Shimerlik & Nolan , 1976), (f) probl emsolving strategies (e.g., Olshavsky , 1977), and (g) self-reference strategies (e.g., Meichenbaum , 1975;Rogers , 1977). Good literature reviews in this area are provided by Bernstein (1973), Faw andWailer (1976), andShininerlik (1978).…”
Section: Study~ Skillsmentioning
confidence: 99%